Main Approaches and Stages of Prototyption: the Example of Designing and Creating Automatic System for Fabric Transfer Patterns - V. Moroz, V.; V. Baulina, L. (International Journal of Engineering and Technology, 2018)
Â This article gives a detailed description of the main approaches and the sequence of manufacturing prototypes of new devices by the example of creating a new device - an automatic patterning system for fabric. Both amateur and industrial ways of solving this problem are described. The basic steps of development of the device from the description of idea, definition of purposes and tasks of development, before creation of the prototype are resulted. Description of the stages of virtual modeling and visualization, the main methods and principles of prototype creation are also presented.Â Â